The combined effect of marble powder and polypropylene fibre on the properties of self-compacting repair mortar - Fatiha Bendjilali; Mohamed Said Mansour; Ali Makhlouf; Mohamed Ghrici; Akram Salah Eddine Belaidi (Journal of Engineered Fibers and Fabrics)
Durability and service life of structures are guaranteed towards the reparation and rehabilitation of concrete. Repair materials are usually cementitious matrixes reinforced with fibres. Partial replacement of cement by supplementary cementitious materials in repair products is important to decrease the consuming of cement, conserve natural resources, reduce waste as well as assisted to advanced sustainable building materials. For this purpose, six self-compacting repair mortar (SCRM) reinforced by polypropylene fibre (PPF) were prepared with replacement of cement by marble powder (MP) at different percentages 0%, 10%, 15%, 20%, 25% and 30% according to the EFNARC 2005 specifications. First, the optimization of fibre’s dosage is obtained at fresh and hardened states (compressive and flexural strength) at 28 days. Then, SCRM reinforced by polypropylene fibres was evaluated in different methods, at fresh states (slump flow) and hardened states (compressive and flexural strength and elasticity modulus) at 3, 7, 28 and 90 days. In addition, durability was studied on sorptivity at 28 days and adhesion strength on composite specimens (half SCRM/half substrate mortar) at 7, 28 and 90 days. The obtained results of fresh mortar revealed that the addition of PPF contributed to workability enhancement. The combined use of PPF and MP showed good mechanical properties of SCRM which fulfilling the requirements of class R4 materials for structural repair products. On the other side, elasticity modulus has decreased with the increment of marble powder content however, a good correlation is attained between elasticity modulus and compressive strength. Adhesion test indicated that 15% of MP is the optimum dosage which provides 20% of gain in adhesion strength.